PEMBELAJARAN MATERI EKOSISTEM DENGAN JIGSAW MELALUI HYPERMEDIA DAN MODUL DITINJAU DARI KEMAMPUAN MEMORI DAN INTERAKSI SOSIAL SISWA - Lukitaningsih, Tri (Jurnal Florea, 2014)
The objectives of the research were to know: 1) the effect of Jigsaw learning through Hypermedia and module towardÂ studentâs achievement; 2) the effect of high and low memory ability towardÂ studentâs achievement; 3) the effect of high and low social interaction towardÂ studentâs achievement; 4) interaction between learning media and memory ability toward studentâs achievement; 5) interaction between learning media and social interaction toward the studentâs achievement; 6) interaction between memory ability and student social interaction toward the studentâs achievement; 7) interaction between learning media and memory ability and student social interaction toward the studentâs achievement. The research sample was determined by random cluster sampling technique that consists of two classes. Data collection techniques for achievement tests and memory skills, social interaction questionnaire for. Anova test hypotheses using 2x2x2 factorial design with the help of software Minitab 15.1.2. Based on the research were concluded : 1) Â There was an effect of with hypermedia and module toward the studentâs achievement. 2) There was no effect of memory ability to ward studentâs achievement. 3) There was an effect of social interaction Â toward studentâs achievement. 4) There was no interaction between learning media and studentâs memory ability toward studentâs achievement. 5) There was no interaction between learning mediaÂ and social interaction toward studentâs achievement. 6) There was no interactoin memory ability and social interaction Â toward studentâs achievement. 7) There was no interaction memory ability, social interaction, and learning mediaÂ toward studentâs achievement .Â Keywords: Â jigsaw, memory ability, social interaction, hypermedia, module.